2014
DOI: 10.1186/bf03352418
|View full text |Cite
|
Sign up to set email alerts
|

Crustal structure in the Siwalik Himalayas using magnetotelluric studies

Abstract: Tectonics in the Himalayan foothills is a result of the compressional forces active since the collision between Indian and Eurasian plates and is best understood as a combination of thin skin tectonics and the basement level faulting. In order to delineate the depth extent of various thrusts and faults, wide band Magnetotelluric (MT) studies were conducted at 17 stations over the Una-Mandi profile located in the Lesser Himalayas. These studies indicate that the Palampur thrust may be a composite of two thrust … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 9 publications
2
6
0
Order By: Relevance
“…Active convergence is accommodated on the Main Boundary Thrust (MBT) and Main Frontal Thrust (MFT) and the models of Israil et al (2008) and Patro and Harinarayana (2009) show northward dipping conductors that are probably due to underthrust sedimentary rocks units in the footwalls of these thrust faults. Similar structures were reported by Gokarn et al (2002b) in the Siwilak Himalaya. Higher resistivities are observed where higher grade metamorphic and igneous rocks are mapped to the North.…”
Section: Mt Studies Of the Central Himalayasupporting
confidence: 85%
“…Active convergence is accommodated on the Main Boundary Thrust (MBT) and Main Frontal Thrust (MFT) and the models of Israil et al (2008) and Patro and Harinarayana (2009) show northward dipping conductors that are probably due to underthrust sedimentary rocks units in the footwalls of these thrust faults. Similar structures were reported by Gokarn et al (2002b) in the Siwilak Himalaya. Higher resistivities are observed where higher grade metamorphic and igneous rocks are mapped to the North.…”
Section: Mt Studies Of the Central Himalayasupporting
confidence: 85%
“…Webb (2013) described the Bilaspur and Palampur Thrusts as a 'thrust system'. Gokarn et al (2002) reported through magnetotelluric studies that the Palampur Thrust could be two thrust zones and that they reached c. 8 km depth. Webb (2013) designated the Bilaspur Thrust as an out-of-sequence thrust.…”
Section: Sub-himalayamentioning
confidence: 99%
“…Reddy and Arora (1993) reported basement depth from 10.0 to 15.0 km below the Himalayan collision region with a high conductivity layer embedded in the crust at using geomagnetic deep sounding (GDS). Gokarn et al (2002) also observed the basement depth increases upto 15.0 km using magnetotelluric (MT) studies. Khattri et al (1989) also suggested the depth of detachment of 15.0-18.0 km underneath the Lesser Himalaya of Garhwal.…”
Section: Interpretation Of Gravity Datamentioning
confidence: 84%
“…Various authors (Tripathi et al 2012, Chamoli et al 2011, Arora et al 2007, Gokarn et al 2002 had carried out the depth estimation and provided their views. However, the present study provides better results and detailed information of source depth locations and structural boundaries with dip information.…”
Section: Interpretation Of Gravity Datamentioning
confidence: 99%